2017
DOI: 10.11604/pamj.2017.27.9.10817
|View full text |Cite
|
Sign up to set email alerts
|

Prise en charge péri-opératoire de l’atrésie de l’œsophage: petits pas non négligeables à Madagascar

Abstract: La prise en charge de l'atrésie de l'œsophage est encore limitée par la précarité des plateaux techniques à Madagascar. Les cas décrits dans ce travail ont pour objectif de relater nos possibilités thérapeutiques et de décrire les progrès à réaliser pour optimiser le traitement de cette pathologie congénitale. Nous avons recueilli tous les dossiers ayant pour motif d’entrée au service de Réanimation Chirurgicale du CHU JRA, Antananarivo, une atrésie de l’œsophage. Nous en avons retenu les tous premiers cas qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
3
0
0
Order By: Relevance
“…This mortality is comparable in Sub-Saharan Africa to Fall et al [25] in Senegal (72%), Bandre et al [6] in Burkina Faso where the mortality was 76%. Randriamizao et al [26] in Madagascar had also found similar mortality to ours (76.5%). It was, however, higher than that of Osei-Nketiah et al [27] in Ghana (59.7%) and significantly higher than that reported by Tönz et al [20] in Switzerland (14%) and by Gottrand et al [28] in France, where it rarely exceeds 5-10% in recent years.…”
Section: Surgical Procedures and Outcomesupporting
confidence: 90%
See 2 more Smart Citations
“…This mortality is comparable in Sub-Saharan Africa to Fall et al [25] in Senegal (72%), Bandre et al [6] in Burkina Faso where the mortality was 76%. Randriamizao et al [26] in Madagascar had also found similar mortality to ours (76.5%). It was, however, higher than that of Osei-Nketiah et al [27] in Ghana (59.7%) and significantly higher than that reported by Tönz et al [20] in Switzerland (14%) and by Gottrand et al [28] in France, where it rarely exceeds 5-10% in recent years.…”
Section: Surgical Procedures and Outcomesupporting
confidence: 90%
“…The lack of postoperative neonatal respiratory support explained the rather high level of extubation on the table in our setting. This was similar to the practice reported in Madagascar by Randriamizao et al [26] where extubation in the operating room, as soon as the patient woke up after the anaesthesia, was performed because of the lack of postoperative neonatal respiratory support. Oxygen weaning was completed when the 21% oxygen saturation was greater than 92%, without respiratory distress [26].…”
Section: Surgical Procedures and Outcomesupporting
confidence: 83%
See 1 more Smart Citation